4H-Quinolizin-4-one Derivatives: A Review - A. Alnajjar, Radwan; S. M. Kawafi , Nagwa (Libyan Journal of Science &Technology, 2022)
In this literature review, Synthesis and analysis of new 4H-quinolizin-4-one derivatives and structural determination using NMR spectroscopy, mass spectroscopy, also the purification of these products by chromatography and finally, bioactivity testing will be discussed.